دعوى تسرب الماقبليات الدينية إلى السنة النبوية – عرض ونقد - رمضاني، محمد (الهيئة العامة للأوقاف والشؤون الإسلامية بدولة ليبيا, 2025)
تتغيَّا هذه الورقة البحثية مناقشة إحدى المزاعم المركزيّة في الخطاب الاستشراقي، والخطابات المناوئة للتراث في العالم العربي (الحداثة، العلمانية، الاتجاه الشيعي المعاصر، القرآنيون ...)، وهي الدعوى بأنَّ كثيرا من المضامين العقدية والفقهية التي تحملها الأحاديث النبوية هي في الحقيقة وافدة من الفضاء الديني اليهودي والنصراني تسربت إلى المدونة الحديثية عن طريق مسلمة أهل الكتاب من الرواة كعبد الله بن سلام رضي الله عنه، وكعب الأحبار ووهب منبه رحمهما الله، وغيرهما من النقلة ممن كانت لهم خلفية دينية سابقة. فالمرادُ بالماقبليات الدينية: الموروثات الدينية السابقة للإسلام، والمنتمية – أساسا - إلى اليهودية والنصرانية المحرَّفتين، والتي تتدعي الخطابات المناوئة للتراث أنها تسربت إلى السنة النبوية بفعل رواة الحديث. وتستند هذه الدعوى على التشابه الموجود بين النصوص اليهودية والمسيحية وبين بعض الأحاديث النبوية في البنية والدلالة، وتحمّلُ منهج النقد الحديثي جريرة الفشل في اكتشاف تسّرب هذه النصوص ومن ثم فرزها وتحييدها. وهذه الفرضية – كما ذكرنا - حاضرة بكثافة في إنتاج المستشرقين بدءًا ب "جولدتسيهر"، "ألفريد غيوم"، "جيمس أندرسون"، و"جوزيف شاخت"ـ وهي تتردد كذلك في كتابات خصوم السنة على اختلاف توجهاتهم الفكرية أمثال: إسماعيل أدهم، محمود أبو رية، محمد أركون، عبد المجيد الشرفي، حمادي الذويب، مصطفى بوهندي .. وغيرهم. وسيسعى هذا البحث إلى عرض هذه الدعوى ببيان جذورها وأدلة القائلين بها، مستخرجة من كتبهم، ثم مناقشتها على ضوء قواعد المنهج العلمي وقواطعِ العقل والتاريخ. Abstract: This research paper aims to discuss one of the central claims in Orientalist discourse and in anti-heritage trends in the Arab world (such as modernism, secularism, contemporary Shi‘i thought, and Qur’an-only movements). This claim argues that many theological and legal contents found in Prophetic Hadiths were in fact borrowed from Jewish and Christian religious traditions and entered the Hadith corpus through converts from the People of the Book, such as ʿAbdullāh ibn Salām, Kaʿb al-Aḥbār, Wahb ibn Munabbih, and others who had prior religious backgrounds. By “religious antecedents” is meant pre-Islamic religious legacies—mainly from distorted Judaism and Christianity—which anti-heritage discourses allege infiltrated the Prophetic Sunnah through Hadith transmitters. This claim is based on perceived similarities in structure and meaning between Jewish and Christian texts and certain Prophetic Hadiths, while accusing the Hadith critical methodology of failing to detect and isolate such infiltrations. This hypothesis appears extensively in Orientalist writings, beginning with Goldziher, Alfred Guillaume, James Anderson, and Joseph Schacht, and is echoed in the works of critics of the Sunnah with diverse intellectual orientations, such as Ismail Adham, Mahmoud Abu Rayya, Mohammed Arkoun, Abdelmajid Charfi, Hammadi Al-Dhuwaib, Mustafa Bouhandi, and others. This study seeks to present this claim by outlining its roots and the evidence cited by its proponents from their own works, then critically examine it in light of the principles of scientific methodology and decisive rational and historical arguments.
مداخلة
Keywords: السنة النبوية; الأحاديث النبوية